Use of telemonitoring technologies in primary health care strategy in the Covid-19 pandemic: an experience report (Research, Society and Development, 2021)
This study aimed to report the experience in the implementation of telemonitoring in Primary Health Care in the Covid-19 pandemic and how the soft, soft-hard and hard technologies played a key role in ensuring comprehensive and longitudinal care for users of the Unified Health System. This report happened between May 2020 and February 2021, in the city of Camaçari, state of Bahia, and assisted about 1.259 individuals in the territory covered by the health unit. It was observed that the use of technologies aimed to offer not only the maintenance of assistance, but also the strengthening of bonds between professional and each users, organization of service and care management, minimization of injuries and strengthening of communication between user and health team. For these reasons, this digital tool reflects a potential to be useful and explored in other scenarios, after the pandemic period.